TELEHEALTH: A PERMANENT EDUCATION STRATEGY APPLIED TO THE PRACTICES AND REORGANIZATION OF THE BASIC CARE WORKING PROCESSES IN THE STATE OF BAHIA: uma estratégia de educação permanente aplicada às práticas e reorganização dos processos de trabalho na atenção básica no estado da Bahia - Matos, Rosivan; Silva, Angélica Baptista (Informação em Pauta, 2019)
ABSTRACT The role of telehealth in the training of primary care professionals in Bahia includes the provision of services through the dimensions of teleconsultation, tele-education and telediagnosis, as well as its sub-dimensions related to Second Formative Opinion (SOF) and Field Monitoring ( Support to the municipalities) with activities directed to all categories of health professionals in Primary Care (PH), who compose, act in programs and strategies of the Ministry of Health in the municipalities of Bahia. Permanent Education (PE) is a powerful tool of the Unified Health System (SUS) that enables the transformation and qualification of health practices, capable of allowing individual and institutional development, being a transformative agent in the re-organization of the work process that can contribute to health worker training. The training of professionals in the use of their services takes place through face-to-face and distance training (web-lectures), operated under an online platform. . This Health Assessment Project consists of verifying and responding to the role of Tele-education provision through telehealth in improving the qualification of health services, identifying services according to the management tool proposal. Keywords: Telehealth 1. Permanent Education 2. Basic Attention 3.